Post flash flood survey: the 14th and 15th October 2015 event in the Paupisi-Solopaca area (Southern Italy). Issue 2 (30th November 2017) - Santo, Antonio; Santangelo, Nicoletta; Forte, Giovanni; De Falco, Melania
ABSTRACT: In this paper, a 1:5000 map of the geomorphic consequences of the 14th–15th October 2015 flash flood is presented. The most severely affected area (about 13 km 2 ) was located at the footslope of Mt. Camposauro (Southern Italy), between the municipalities of Solopaca and Paupisi. In this area high-intensity and very localized cloudbursts of short duration induced hillslope erosion and sediment delivery from the slopes to the Calore River, activating several alluvial fans. The rainstorm lasted 7 h with a maximum recorded rainfall peak of nearly 140 mm in 2 h. The event map resulting from a geological and geomorphological post-event field survey was supported by satellite images and unmanned aerial vehicle image interpretations, respectively taken one day and one week after the event. The flash flood resulted in no casualties but severely affected the local economy, mainly based on agriculture and wine production.